Anak Gelandangan sebagai Objek Seni Lukis Kontemporer - Hania, Natasa; Hafiz, Abd. (YASIN, 2023)
The purpose of making this final work is to visualize homeless children in contemporary painting. This is a form of the author's anxiety towards homeless children about how the activities of small children have tried to find food for themselves. In essence, young children should be in a decent position for their life. But in the field there are many cases of homeless children who work, because there is no family that provides enough for their needs. The creation method for the final work is carried out in stages, namely the preparation stage by seeking information, elaboration by analyzing problems, synthesizing establishing ideas, realizing concepts by creating works of contemporary painting and finishing by holding exhibitions. Ten works of painting with a size of 100 cm x 120 cm in acrylic on canvas based on the theme "social phenomena" in accordance with a predetermined idea about the activities of homeless children were developed through ten titles "consistent", recalculating", "carrying a burden", “for mother's sake”, “must be strong”, “want to play”, “my wheelbarrow and my uniform”, “thank you Allah”, “my sister is crying hungry”, hope.